(untitled) (Edad Media. Revista de Historia, 2018)
Historiography has assessed the 1479 royal pardon as one more episode in the historical commonplace that is the completion of the pacification of the kingdom in 1480 by the Catholic Monarchs. Far from questioning the said pacification, for which I consider there is indisputable evidence, in this essay I intend to delve deeper into the meaning, consequences, and terms of the pacification. For this, I have availed myself of the detailed accounts given in the Burgos books of records in order to analyze the reach of this royal pardon, as well as the reaction of the Burgalese society. I hold that this process entailed a remarkable intensification of the progressive “nobilization” of the royal cities which would reinforce the parallelism between centralization and lordliness that I consider to have been the driving thread in the genesis, at the end of the fifteenth century, of the centralized feudal monarchy, also called the Modern State or the Hispanic Monarchy.